2010
DOI: 10.1111/j.1365-246x.2010.04540.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially ordered single-frequency 2-D acoustic waveform inversion in the Laplace-Fourier domain

Abstract: S U M M A R YIn the conventional frequency-domain waveform inversion, either multifrequency simultaneous inversion or sequential single-frequency inversion has been implemented. However, most conventional frequency-domain waveform inversion methods fail to recover background velocity when low-frequency information is missing. Recently, new waveform inversion techniques in the Laplace and Laplace-Fourier domain have been proposed to recover background velocity structure from data with insufficient low-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Because the data were acquired on 3D elastic media, the elastic waves and the 3D geometric spreading of the amplitude can serve as the noise. However, it has been shown that the Laplace-domain inversion can yield an accurate large-scale velocity model from field data sets (Shin and Cha, 2008;Shin et al, 2010) and synthetic marine data with elastic waves (Ha et al, 2010b).…”
Section: Field Data Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Because the data were acquired on 3D elastic media, the elastic waves and the 3D geometric spreading of the amplitude can serve as the noise. However, it has been shown that the Laplace-domain inversion can yield an accurate large-scale velocity model from field data sets (Shin and Cha, 2008;Shin et al, 2010) and synthetic marine data with elastic waves (Ha et al, 2010b).…”
Section: Field Data Examplementioning
confidence: 99%
“…Those inversion results can be used as an initial model for conventional full-waveform inversions (Shin and Ha, 2008). It can produce high-resolution velocity models when combined with the frequency-domain inversion method (Shin and Cha, 2009;Shin et al, 2010). The method is very sensitive to the noise before the first arrival due to the damping function in the Laplace transformation (Shin and Cha, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies have been devoted to develop a robust waveform inversion algorithm. Among them, Shin and Min (2006) proposed the logarithmic waveform inversion in the frequency domain, and it has been widely applied in both the frequency and Laplace domains Cha, 2008, 2009;Shin et al, 2007;Shin et al, 2010). Taking the logarithm of a wavefield separates the amplitude (real part) and phase (imaginary part) of the Fourier transformed wavefield, where the amplitude and phase are related to the energy and kinematic properties of the wavefield, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The success of Laplace-domain FWI lies in that (1) the objective function in Laplace domain is much smoother than its frequency-domain counterpart, thus considerably mitigating the problem of local minima (Shin and Ha, 2008); (2) Lapace-domain FWI is less sensitive to the lack of low-frequency information in real seismic data in comparison with Fourier-domain FWI . Combined with conventional FWI, Lapace-domain FWI has made important contributions to the successful application of FWI to real data (Shin and Cha, 2009;Shin et al, 2010;.…”
Section: Introductionmentioning
confidence: 99%